PsycEXTRA Dataset 1999
DOI: 10.1037/e445332005-001
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the command and Control Vehicle (C2V) operational environment on soldier health and performance

Abstract: Approved for public release; distribution is unlimited. AbstractThe command and control vehicle (C2V) was developed to support U.S. Army tactical operation centers in heavy forces. The requirements for the C2V stipulate that it must support mobile operations and that it must support command and control (C2) from within the confines of the vehicle. However, in early testing, some human operators exhibited motion sickness during moving operations. As a result, the Human Research and Engineering Directorate of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 10 publications
4
28
0
Order By: Relevance
“…Motion sickness in a command and control vehicle (C2V) has been investigated by Cowings et al 9) , who found that while incidences of emesis were rare, many of the subjects reported drowsiness and mild nausea. Performance on cognitive tasks in a C2V has also been studied [10][11][12] , but the results have been ambiguous. In these studies, the details of the vibration spectra were not reported.…”
Section: Introductionmentioning
confidence: 99%
“…Motion sickness in a command and control vehicle (C2V) has been investigated by Cowings et al 9) , who found that while incidences of emesis were rare, many of the subjects reported drowsiness and mild nausea. Performance on cognitive tasks in a C2V has also been studied [10][11][12] , but the results have been ambiguous. In these studies, the details of the vibration spectra were not reported.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, previous research has already shown that the use of in-vehicle entertainment systems can increase the incidence and severity of carsickness. Cowings et al (1999), for example, reported a negative impact on crew performance and health when subjects attended to displays while the vehicle was moving. More recently, in a study by Kato and Kitazaki (2008), participants were driven around whilst sitting in the backseat either watching the road ahead, or a rear-seat display showing written text.…”
Section: Visual-vestibular Conflictmentioning
confidence: 99%
“…Seasickness has been positively correlated with motion sickness caused by other modes of transportation; however, the motion stimulus involved with seasickness often elicits more severe symptoms than stimuli from airplanes, trains, and cars (Pethybridge, 1982). Finally, in recent studies examining military land maneuvers in amphibious assault vehicles, 74% of Marines reported moderate to severe symptoms, such as headache, nausea, malaise, anorexia, and emesis, while working at computer workstations (Cowings, Toscano, & DeRoshia, 1998;Cowings, Toscano, DeRoshia & Tauson, 1999;Rickert, 2000). Rickert (2000) and Schipani, Bruno, Lattin, King and Patton (1998) demonstrated that military personnel conducting mission operations in this provocative motion environment exhibited significant performance decrements on cognitive tasks requiring time sharing, selective attention, inductive reasoning, memorization and spatial orientation.…”
Section: Impact Of Motion Sickness On the Military And Astronautsmentioning
confidence: 99%